Efficacy of various sequences of transcatheter arterial chemoembolization combined with PD-1 inhibitors in advanced hepatocellular carcinoma: a retrospective analysis - Zhu, Heping; Hu, Shenping; Wang, Fuqiang; Yin, Zhenyu (Frontiers in Medicine, 2025)
BackgroundWe aimed to explore whether the diverse sequences of Transcatheter Arterial Chemoembolization (TACE) combined with Programmed Death-1 (PD-1) inhibitors impact the prognosis of advanced hepatocellular carcinoma (HCC).MethodsIn this single-center retrospective study, we collected data from patients with advanced HCC who underwent TACE combined with PD-1 inhibitors and categorized them into a group treated with PD-1 inhibitors after TACE (T+P) and a group treated with TACE after PD-1 inhibitors (P+T). Kaplan–Meier and logistic analyses were used to investigate the differences in treatment efficacy.ResultsUltimately, a total of 27 eligible patients were included in this study. Among them, 8 patients (29.6%) were in Barcelona Clinic Liver Cancer (BCLC) stage B, 19 patients were in stage C, 22 patients (81.5%) were in Child-Pugh stage A, five patients were in stage B,15 patients (55.6%) were in the P+T group, and 12 patients (44.4%) were in the T+P group. After a median follow-up of 5.0 months (1.8–17.3), all patients exhibited disease progression. According to the RECIST v1.1 criteria, the 6-month Disease Control Rate (DCR) in the T+P group and the P+T group was 58.3 and 20% (p = 0.048); the median Progression-Free Survival (PFS) in the two groups was 6.0 months (95% CI 5.32–6.67) and 4.2 months (95%CI 2.91–5.4) (HR, 2.59; 95% CI 1.10–6.10, p = 0.029).ConclusionThe effect of the T+P treatment was superior to that of the P+T treatment. Different sequences of TACE combined with PD-1 inhibitors influence the prognosis of patients with advanced HCC.